Tropical Cyclone Activities Over the Western North Pacific in Summer 2020: Transition From Silence in July to Unusually Active in August - Gong, Zhensong; Liu, Yunyun; Hu, Zeng-Zhen; Liang, Ping (Frontiers in Earth Science, 2022)
In the summer of 2020, tropical cyclone (TC) activities experienced a contrastive transition over the western North Pacific (WNP), from silence in July to unusually active in August. Furthermore, the generation location of TCs was further northwestward in August 2020, resulting in more typhoons landing, and three TCs successively moving northward, which is rare in history. Based on diagnoses with the total genesis potential index (GPI) in July and August 2020, it is suggested that the variation of mid-tropospheric relative humidity and upward convective motion is the major factor for the transition of TC genesis in summer 2020, while the changes of SST, low-level vorticity, and vertical wind shear anomalies played a secondary role. The exceptional variation of the Madden–Julian Oscillation (MJO) activity from July to August 2020 contributed to the transition of the environmental conditions over WNP. In July 2020, MJO was restricted in the Indian Ocean, thus generating an anomalous low-level anticyclone over WNP that intensified the WNP subtropical high. While in early August, MJO propagated eastward to enhance convective activities over the South China Sea and the Philippine Sea, favorable to TC genesis. Thus, MJO activity is a potential predictability source for intraseasonal variation of TC genesis anomalies in WNP.